2020
DOI: 10.1002/jmri.27288
|View full text |Cite
|
Sign up to set email alerts
|

Primary Central Nervous System Lymphoma: Clinical Evaluation of Automated Segmentation on Multiparametric MRI Using Deep Learning

Abstract: Background: Precise volumetric assessment of brain tumors is relevant for treatment planning and monitoring. However, manual segmentations are time-consuming and impeded by intra-and interrater variabilities. Purpose: To investigate the performance of a deep-learning model (DLM) to automatically detect and segment primary central nervous system lymphoma (PCNSL) on clinical MRI. Study Type: Retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…8 A large number of recently proposed deep learning algorithms enabling automated detection of BMs cannot generate segmentations of tumor tissue. [28][29][30] In contrast, the DLM of the present study provides 3D voxel-wise segmentations of BMs with a performance (DSC of 0.72), which is in line with the present literature (0.67-0.79 25,26 ) and comparable to DL-based segmentation of larger malignant tumors, eg, glioblastoma (0.62-0.86 21 ) or primary central nervous system lymphoma (0.73-0.76 20 ). In this context, automated segmentation of BMs might be useful for lesion contouring in stereotactic radiosurgery, leading to a reduction of time effort as well as of intra-and inter-rater variabilities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…8 A large number of recently proposed deep learning algorithms enabling automated detection of BMs cannot generate segmentations of tumor tissue. [28][29][30] In contrast, the DLM of the present study provides 3D voxel-wise segmentations of BMs with a performance (DSC of 0.72), which is in line with the present literature (0.67-0.79 25,26 ) and comparable to DL-based segmentation of larger malignant tumors, eg, glioblastoma (0.62-0.86 21 ) or primary central nervous system lymphoma (0.73-0.76 20 ). In this context, automated segmentation of BMs might be useful for lesion contouring in stereotactic radiosurgery, leading to a reduction of time effort as well as of intra-and inter-rater variabilities.…”
Section: Discussionsupporting
confidence: 90%
“…Further, in this study, only MRI data at primary diagnosis of the BMs were included with unknown performance of the DLM after therapy. However, the DeepMedic architecture has already shown its potential for application in longitudinal tumor imaging in primary central nervous system lymphoma 20 . Finally, compared with other deep learning based approaches to automatically detect BMs, 25,30 the DeepMedic network requires multiparametric MRI datasets (FLAIR, T 1 ‐/T 2 ‐weighted, and T 1 CE).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aneurysm detection on CTA proves to be challenging with misdiagnosis of aSAH eventually resulting in a poor clinical outcome, automated detection of intracranial aneurysms may be of valuable assistance to physicians [11][12][13][14]. Over the last decade, deep learning models (DLMs), in particular convolutional neural networks (CNNs), have shown great potential in performing diagnostic and analyzing tasks on medical imaging for different subspecialties [15][16][17][18]19].…”
Section: Introductionmentioning
confidence: 99%
“…20 Using deep learning based segmentation algorithm had the potential to realize automatic tumor delineation, however, the previous brain tumor segmentation studies mainly focused on the GBM segmentation, and the performance of PCNSL segmentation had Dice similarity coefficient lower than 0.8, which indicated a not ideal results that needed further manual correction. 21,22 By utilizing convolutional neural networks (CNN), image features can be extracted without the delineation of ROIs. 23 For brain tumor diagnosis, previous studies have shown the CNN could be used for glioma grading and genetic mutation classification.…”
mentioning
confidence: 99%